State of knowledge of 19th Century higher education historiography in Tamaulipas - Álvarez-Cervantes, Luisa (Universidad Autónoma de Tamaulipas, 2021)
The state of Tamaulipas is located in the northeast geographical region of Mexico, which was colonized several years after the center and south of the country. Little has been documented of the historical evolution of the first higher education institutions of the state. The aim of this work is to show the current state of knowledge of the historiography of education in Tamaulipas in the 19th century. Twenty-two edited and published works, which collected memories and educational experiences between 1948 and 2018 were found. They underwent a procedure, based on historiographic criteria, which allowed their classification into histories, biographies, chronicles, or memoirs. They were grouped according to spaces and temporalities in general or regional, and by historical periods of education. The works that discuss each of  the stages are described as follows: those of the initial stage, referring to the founding of the first institutions by illustrated republican teachers were written by its graduates, historians by vocation, authors of the first histories of state education, who worked within an enlightened, liberal, republican and juarista framework, promoter of offering the people a public, secular, free and compulsory education, in which higher education in the state was institutionalized. The second stage occurred in the 20th century, with the creation of the University of Tamaulipas, which would later become the Universidad Autónoma de Tamaulipas, an institution that educates professional historians, history teachers and historians of nineteenth-century roots, which complement the historical educational framework. This work provides a starting point for the researcher who is interested in continuing with the line of history and historiography of this time and space.